Artikel Review : Studi Fitokimia Dan Aktivitas Farmakologi Pada Tanaman Bidara (Ziziphus Mauritiana Lamk) - Windi Tri Wahyuni; Fina Nikmatul Wasi’ah; Ismatun Maulidiyah; Elsa Saqila; Sirojul Eilma; Oktafia Damayanti; Brelianty Nevy; Silvi Novita; Agustinus Alfred Seran; Ivan Charles S.Klau; Arista Wahyu Ningsih (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Background: The Bidara plant (Ziziphus mauritiana Lam) is a plant that can be used as a traditional medicine for the treatment of various diseases. Apart from that, the Bidara plant is one type of plant that has the widest distribution and has high economic value. According to several research results, Bidara leaves contain many compounds found in Bidara plants, including saponins, flavonoids, tannins, alkaloids and phenols. Objective: This review journal aims to determine the compounds contained in each part of the Bidara plant and their pharmacological activity. Method: The method used in this article is the literature review method. Results: In this journal review article, there is discussion about Bidara (Ziziphus mauritiana Lam) especially on pharmacological activities such as antibacterial, antimicrobial, antidepressant, anticancer, antipyretic, analgesic, anti-inflammatory and antioxidant in parts of the Bidara plant. Conclusion: in several of these reviews it can be concluded that the part of the Bidara plant that contains many ingredients and has many benefits is the leaves.